2019
DOI: 10.37358/mp.19.3.5219
|View full text |Cite
|
Sign up to set email alerts
|

Composites of Styrene-butadiene Block-copolymers Reinforced with WEEE Polystyrene Fraction

Abstract: The high global production of electric and electronic equipment increases in the same manner the amount of the waste that needs to be recycled. Special attention is given to the plastics recycling from the waste in addition to the metals recovery that brings economic advantages. Considering that the plastic amount contains about 80% polystyrene polymers, the paper presents a recycling study of this fraction as reinforcing agent for a styrene-butadiene block copolymer. In order to reduce the melt viscosity, som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…The reinforcement study with the non-metallic fraction of WPCB was carried out in the tetrahydrofuran solution of the SBS block-copolymer of concentration 20%. The dosage of the reinforcing filler was achieved in steps of 5% to 30%, the maximum limit being imposed by the maintenance of polybutadiene as the continuous phase of the extended or un-extended composite material with white-heavy oil [22,23].…”
Section: Methodsmentioning
confidence: 99%
“…The reinforcement study with the non-metallic fraction of WPCB was carried out in the tetrahydrofuran solution of the SBS block-copolymer of concentration 20%. The dosage of the reinforcing filler was achieved in steps of 5% to 30%, the maximum limit being imposed by the maintenance of polybutadiene as the continuous phase of the extended or un-extended composite material with white-heavy oil [22,23].…”
Section: Methodsmentioning
confidence: 99%
“…As can be seen in Figure 2, from 2018 onwards, an increasing trend in the number of publications was recorded. A deep analysis indicates that the focus was on topics such as circular economy [25,[56][57][58][59][60][61], as well as the recycling of contaminated plastics (e.g., from e-waste and agricultural packaging) [15,24,[62][63][64][65][66][67][68][69][70][71][72]. to the literature review is to target some, yet not all, of the published scientific articles and online reports on the main topics of plastics recycling, circular economy of plastics, and challenges to plastic waste recycling.…”
Section: State-of-the-art In Literature and Trends Towards Plastic Recyclingmentioning
confidence: 99%
“…By-product and waste recycling is an urgent and rapidly emerging concern for the future of human kind [4], in this sense, different authors have proposed various solutions for the environment regarding the reuse of many types of waste [5][6][7][8][9]. Recently, a number of research studies have identified alternative ways of managing ceramic waste byreusing it in the production of alternative construction materials [10][11][12] or to develop new binding systems based on red clay bricks [13].…”
Section: Introductionmentioning
confidence: 99%